1993
DOI: 10.1093/jn/123.4.754
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Phosphorus Restriction Prevents Corticomedullary Nephrocalcinosis and Sustains Reproductive Performance but Delays Bone Mineralization in Rats

Abstract: In a long-term experiment with three successive generations of rats, the influence of dietary phosphorus restriction (2 instead of 4 g phosphorus/kg diet) on nephrocalcinosis, reproduction and bone mineralization was studied. Nephrocalcinosis in female rats, as based on kidney calcium concentration and histological examination, was prevented by phosphorus restriction. The low phosphorus diet caused reduced femur concentrations of magnesium, calcium and phosphorus in rats of the first and second generation aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…To overcome the obstacle of rat being phosphate sensitive, we used male rats that are reported to be more resistant to dietary phosphate than females. (19) In fact, the Ca:P 1:2 rats did not have a significant rise in S-PTH compared with controls, although many of the parameters measured declined, indicating that high dietary phosphate intake has a weakening effect beyond PTH.…”
Section: High-phosphate Intake Reduces Bone Strength 89mentioning
confidence: 81%
See 2 more Smart Citations
“…To overcome the obstacle of rat being phosphate sensitive, we used male rats that are reported to be more resistant to dietary phosphate than females. (19) In fact, the Ca:P 1:2 rats did not have a significant rise in S-PTH compared with controls, although many of the parameters measured declined, indicating that high dietary phosphate intake has a weakening effect beyond PTH.…”
Section: High-phosphate Intake Reduces Bone Strength 89mentioning
confidence: 81%
“…Male rats were used because they are reported to be relatively insensitive to diet-induced nephrocalcinogenesis, which could produce interindividual variation in results. (19) BMD measurement with DXA Right femur bone area (cm 2 ), bone mineral content (BMC, g), and bone mineral density (BMD, g/cm 2 ) were determined in vivo with a dual-energy X-ray bone densitometry device (Lunar PIXImus; GE Medical Systems). Analyses of the areas were carried out with the image of the animal on the screen using a region of interest for the segments.…”
Section: Animals and Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adult female rats have the role to breed offspring. In a study of three successive generations of rats, Ritskes-Hoitinga et al 15) have reported that 0.2% P in the diet sustained reproduction, but delayed bone mineralization in the first-and second-generation offspring after 4-12 week compared to 0.4% P in the diet. It was suggested that keeping the serum P concentration at the normal level might be necessary to sustain bone mineralization in next-generation offspring, although a low-P diet was effective for bone mineralization in adult females.…”
mentioning
confidence: 99%
“…3 High-phosphate diets also can induce nephrocalcinosis in rats. 22 Hyperphosphaturia is a hallmark of XLH. 1 In our study, HCTZ therapy decreased urinary calcium excretion without affecting phosphate excretion measured by TmP/GFR (Table 1).…”
Section: Discussionmentioning
confidence: 99%